Cost-effectiveness of scar management post-burn: a trial-based economic evaluation of three intervention models - Steven M. McPhail; Jodie Wiseman; Megan Simons; Roy Kimble; Zephanie Tyack (Scientific Reports, 2022)
Abstract Optimal burn scar management has the potential to markedly improve the lives of children, but can require substantial healthcare resources. The study aimed to examine the cost-effectiveness of three scar management interventions: pressure garment; topical silicone gel; combined pressure garment and topical silicone gel therapy, alongside a randomised controlled trial of these interventions. Participants were children (n = 153) referred for burn scar management following grafting, spontaneous healing after acute burn injury, or reconstructive surgery. Healthcare resource use was costed from a health service perspective (6-months post-burn time-horizon). The mean total scar management cost was lowest in the topical silicone gel group ($382.87 (95% CI $337.72, $443.29)) compared to the pressure garment ($1327.02 (95% CI $1081.46, $1659.95)) and combined intervention $1605.97 ($1077.65, $2694.23)) groups. There were no significant between-group differences in Quality Adjusted Life Year estimates. There was a 70% probability that topical silicone gel dominated pressure garment therapy (was cheaper and more effective), a 29% probability that pressure garment therapy dominated combined therapy, and a 63% probability that topical silicone gel dominated combined therapy. In conclusion, topical silicone gel was the cheaper intervention, and may be favoured in the absence of clear clinical effect favouring pressure garment therapy or a combination of these management approaches. Trial registration: ACTRN12616001100482 (prospectively registered).